Perceptions of successful domestic and international research grant applications among experienced and novice researchers - Sumeth Suebtrakul; Pornpimon Adams; Pitchapa Vutikes; Boosaree Titapiwatanakun; Paul Adams; Jaranit Kaewkungwal (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The main purpose of the study was to identify the key elements that characterize successful grant proposals and the relative importance of issues that constitute difficulties and concerns in preparing the proposals. The study aimed, in particular, to explore grantsmanship perceptions based on the experiences of researchers in Thailand who had, or had not yet, successfully been awarded domestic and/or international research funding. Design/methodology/approach - Anonymous online questionnaires were distributed to researchers in biomedical and public health fields in Thai academic institutes. The online survey asked the anonymous participants to complete a questionnaire comprising both multiple-choice and open-ended questions. Findings - About 19% of 300 respondents had received both domestic and international research grants, and 60% of domestic research grants. The top 5 issues in grant applications were: (1) choosing a topic that matched the grant opportunity, (2) feasibility of research design and methods, (3) suitable research design and methodology, (4) model and theoretical justification, and (5) ethical considerations. Significant differences in perceptions among researchers were found for the feasibility of research design and methods and proposing a reasonable and justifiable budget. Originality/value - The information derived from this analysis reflected the perceptions of the researchers and may or may not correlate with those of grant agency reviewers. The results of this study may be insightful and instructive for other researchers and form the basis for training and mentoring researchers in informed and effective grantsmanship, particularly novice researchers with limited or no experience in grant proposal writing. This study particularly reflected grantsmanship perceptions among researchers in Thailand. It may also serve to exemplify lessons learned for researchers in other low-income and middle-income countries (LMIC) exposed to similar settings and situations applying for research grants.